Applying the RDA Data Maturity Model on the Core Dataset of the German Medical Informatics Initiative - Michaelis, Lea; Inau, Esther Thea; Muzoora, Michael Rusongoza; Wodke, Judith A.H.; Ganslandt, Thomas; Thun, Sylvia; Waltemath, Dagmar (Proceedings of the 15th International Conference on Semantic Web Applications and Tools for Health Care and Life Sciences (SWAT4HCLS 2024), 2024)
The German Medical Informatics Initiative authored a modularised Core Dataset which enables the sharing of clinical routine data across German hospital sites. In this work, we apply the RDA Data Maturity Model to run a FAIR assessment on one module of the Core Dataset. We summarise the results of this assessment and present the lessons learnt. We anticipate that the assessment will help to design a FAIRification workflow for the Core Dataset and to estimate the overall resources required for that task.
CRIS-Team Scopus Importer:2025-02-04
Keywords: FAIR assessment; FAIR Data Maturity Model; FAIR-IMPACT; Medical Informatics Initiative